Triatoma dimidiata, domestic animals and acute Chagas disease: a 10-year follow-up after an eco-bio-social intervention - Jose G. Juarez; Andrea M. Moller-Vasquez; María Granados-Presa; Pamela Pennington; Norma Padilla; Sujata Balasubramanian; Lisa D. Auckland; Elsa Berganza; Estuardo Alvarado Liberato; Henry Esquivel; Ranferi Trampe; Louisa A. Messenger; et al. (Parasites & Vectors)
Abstract Background Trypanosoma cruzi, the causative agent of Chagas disease, is primarily transmitted by triatomine insects, including Triatoma dimidiata. In Central America, vector control programs have significantly reduced transmission; however, certain regions, such as Comapa municipality, department of Jutiapa, Guatemala, continue to experience persistent T. dimidiata infestation. This study presents a 10-year follow-up assessment of triatomine infestation, T. cruzi infection and acute Chagas disease cases after an eco-bio-social intervention. Methods Between June and August 2022, entomological surveys were conducted in four communities of Comapa municipality. Seventy-six households were systematically searched for triatomines using the one-person hour method. Triatomines were collected and processed for T. cruzi detection using real-time PCR (qPCR), and blood meal analysis was performed to assess host feeding patterns. Dog samples and environmental DNA from household surfaces were also processed for T. cruzi detection. Additionally, surveillance for acute Chagas disease cases was carried out in collaboration with the Ministry of Health. Results Persistent household infestation by T. dimidiata was observed across all four communities, with infestation rates ranging from 17% to 38% and colonization levels ranging from 9% to 29%. The mean household triatomine density remained low, suggesting a possible reduction in transmission risk. A total of 86 triatomines were collected, of which 26% tested positive for T. cruzi (all TcI strain). Amplicon deep-sequencing analysis of the blood meals from triatomines identified seven vertebrate species and one insect family as hosts upon which triatomines had previously fed, with chickens and dogs being the most common blood meal sources (occurring in 85% of triatomines). Of the 132 dogs processed, 22% were positive for T. cruzi (all TcI strain). Two acute Chagas disease cases in children were detected in the surveillance period, including one child in 2015 who remained seropositive in 2022, emphasizing the need for continued surveillance. Conclusions Despite the multiple interventions that have been carried out for over a decade in Comapa municipality, T. dimidiata infestation remains high in the area, with sustained evidence of acute Chagas disease in humans, necessitating continued vector control efforts. The persistence of T. cruzi transmission among triatomines and dogs and the predominant role of chickens and dogs in supporting the vector population highlight the need for innovative control strategies, including those that target domestic animals, to mitigate Chagas disease risk. Graphical Abstract